Comparisons of the Thermomechanical Fatigue Behavior of C/SIC and SIC/SIC Ceramic-Matrix Composites Subjected to Different Phase Angle. (April 2019) - Li, L. B.
ABSTRACT: In this paper, the comparisons of thermomechanical fatigue behavior of C/SiC and SiC/SiC fiber-reinforced ceramic-matrix composites (CMCs) subjected to different phase angles of θ = 0, π/3, π/2 and π have been investigated. The relationships between the fatigue damage mechanisms, phase angle, fatigue hysteresis dissipated energy, fatigue hysteresis modulus and fatigue peak strain, fiber/matrix interface debonding and sliding have been established. The differences between C/SiC and SiC/SiC composites under thermomechanical fatigue loading with different phase angles have been analyzed. The damage accumulation of 2.5D C/SiC and 2D SiC/SiC composites under thermomechanical fatigue loading have been predicted. With increasing of the phase angle, the fatigue hysteresis dissipated energy, fatigue peak strain and interface debonded length decrease for the SiC/SiC composite; however, for the C/SiC composite, the fatigue hysteresis dissipated energy, fatigue peak strain and the interface debonded length increase at the same cycle number.